Information Visualization to support decision making in the context of distance learning: A study with VLE TelEduc - Do Carmo, Alisson Fernando Coelho [UNESP]; Vani, Bruno César [UNESP]; Ferreira, Erik Rafael Alves [UNESP]; Shimabukuro, Milton Hirokazu [UNESP]; Schlünzen Junior, Klaus [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Digital data sets constitute rich sources of information, which can be extracted and evaluated applying computational tools, for example, those ones for Information Visualization. Web-based applications, such as social network environments, forums and virtual environments for Distance Learning, are good examples for such sources. The great amount of data has direct impact on processing and analysis tasks. This paper presents the computational tool Mapper, defined and implemented to use visual representations - maps, graphics and diagrams - for supporting the decision making process by analyzing data stored in Virtual Learning Environment TelEduc-Unesp. © 2012 IEEE.
Keywords: Graphics; Information Visualization; Maps; Virtual Learning Environment; Computational tools; Decision making process; Digital data sets; Direct impact; Information visualization; Social Networks; Sources of informations; Virtual learning environments; Visual representations; Web-based applications; Computational methods; Decision making; Information analysis; Information systems; Virtual reality; E-learning